Improved dendroclimatic calibration using blue intensity in the southern Yukon. (November 2019) - Wilson, R; Anchukaitis, K; Andreu-Hayles, L; Cook, E; D'Arrigo, R; Davi, N; Haberbauer, L; Krusic, P; Luckman, B; Morimoto, D; Oelkers, R; Wiles, G; et al.
In north-western North America, the so-called divergence problem (DP) is expressed in tree ring width (RW) as an unstable temperature signal in recent decades. Maximum latewood density (MXD), from the same region, shows minimal evidence of DP. While MXD is a superior proxy for summer temperatures, there are very few long MXD records from North America. Latewood blue intensity (LWB) measures similar wood properties as MXD, expresses a similar climate response, is much cheaper to generate and thereby could provide the means to profoundly expand the extant network of temperature sensitive tree-ring (TR) chronologies in North America. In this study, LWB is measured from 17 white spruce sites ( Picea glauca ) in south-western Yukon to test whether LWB is immune to the temporal calibration instabilities observed in RW. A number of detrending methodologies are examined. The strongest calibration results for both RW and LWB are consistently returned using age-dependent spline (ADS) detrending within the signal-free (SF) framework. RW data calibrate best with June–July maximum temperatures (Tmax), explaining up to 28% variance, but all models fail validation and residual analysis. In comparison, LWB calibrates strongly (explaining 43–51% of May–August Tmax) and validates well. The reconstruction extends to 1337 CE, but uncertainties increase substantially before the early 17th century because of low replication. RW-, MXD- and LWB-based summer temperature reconstructions from the Gulf of Alaska, the Wrangell Mountains and Northern Alaska display good agreement at multi-decadal and higher frequencies, but the Yukon LWB reconstruction appears potentially limited in its expression of centennial-scale variation. While LWB improves dendroclimatic calibration, future work must focus on suitably preserved sub-fossil material to increase replication prior to 1650 CE.